2021
DOI: 10.31703/gsr.2021(vi-i).08
|View full text |Cite
|
Sign up to set email alerts
|

Inter-generational Attitudinal Shift towards English from Punjabi Language: A Sociolinguistic Study of Lahore, Pakistan

Abstract: The survey study investigates the intergenerational attitudinal shift towards English from the Punjabi language with a focus on three generations (male and female) population of Lahore ageing 55 years and above, 35 to 54 and 15 to 34. A twenty-five questions questionnaire was administered on randomly selected sixty subjects for the quantitative data analyzed qualitatively. The numerical analysis was carried out to see the intergenerational shift towards English from the Punjabi language. For this purpose, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…B a s e d o n t h e i r y e a r s o f language teaching experience, the participants of a study suggested that to promote Punjabi in Pakistan; every Punjabi has the responsibility to speak Punjabi with confidence as they speak English or Urdu and admire others who speak Punjabi rather than stigmatizing others. It was reported that to save Punjabi from social death, it should be taught in schools as well (Naqvi, Nadeem, & Rahman, 2021). Seminars should be conducted to promote the Punjabi language and to save the Punjabi heritage.…”
Section: Discussionmentioning
confidence: 99%
“…B a s e d o n t h e i r y e a r s o f language teaching experience, the participants of a study suggested that to promote Punjabi in Pakistan; every Punjabi has the responsibility to speak Punjabi with confidence as they speak English or Urdu and admire others who speak Punjabi rather than stigmatizing others. It was reported that to save Punjabi from social death, it should be taught in schools as well (Naqvi, Nadeem, & Rahman, 2021). Seminars should be conducted to promote the Punjabi language and to save the Punjabi heritage.…”
Section: Discussionmentioning
confidence: 99%